Perbuatan Melawan Hukum dalam Sengketa Pertanahan: Analisis Mendalam dan Solusi Efektif - Gunawang Gunawang (Jurnal Litigasi Amsir, 2024)
This study aims to analyze the settlement of land disputes in Indonesia, focusing on the legal force of letter proof as the main evidence. The research method used is juridical normative, with a literature study approach to collect and analyze data. The study results show that the settlement of land disputes can be pursued through litigation and non-litigation channels, but both have their obstacles. Proof of letters, especially land certificates, has significant legal force, but its validity is not absolute and needs to be supported by a transparent and accountable verification mechanism. This study emphasizes the importance of synergy between various approaches to dispute resolution, the active role of the government, and the public's understanding of land law to achieve justice and legal certainty.